The Dating and Historical Value of Rouletted Ware - Schenk, Heidrun (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
“Old myths die hard”.H. P. Ray drew this conclusion when describing the “surviving conceptions” on the part of scholars for Indo-Roman trade (H. P. Ray 1999: 317). She refers especially to “all attempts being made to keep the linkage with Indo-Roman trade alive”. Rouletted ware, in the following called RW, is the subject of many articles which deal with early historic trade and contacts; many excavation sites have been dated by means of this distinctive form. And to this day many scholars still regard Arikamedu and RW as well as proof of Indo-Roman trade during the early first centuries A.D., as reflected in the Periplus maris erythreae, despite new divergent results which have come forth within the last 20 years. The uncritical reliance on half a century old publications and/or the non-observance of recent  investigations often leads to a perpetuation of obsolete “classic” conceptions. S. Suresh recently complains about the “non-availability of data pertaining to the precise stratigraphical context of each of the RW sherds on a site-by-site basis”. The present study confirms Ray’s abovementioned criticism and points to the need for a greater awareness of the revised significance of Arikamedu and RW in particular which V. Begley has revealed since 1983. The following remarks rest on the results of the excavations at Tissamaharama, Sri Lanka, and its main focus lies on the RW.The article will be available as a PDF in the near future.